Sebaceous carcinoma of the hand: an extremely rare case - Putra Prameswara, Anak Agung Gede; Ariandi, Mirza; Yurianto, Henry; Saleh, Ruksal (International Journal of Research in Medical Sciences, 2019)
Sebaceous carcinoma is an aggressive tumor derived from adnexal epithelium of sebaceous gland and accounts for 1% of all cutaneous malignancy. Most commonly found at head and neck region. with sebaceous carcinoma in extrimity few than 100 cases have been formally documented. Since this lesion are uncommon, this lession tend to be misdiagnosed. Sebaceous carcinoma is a clinically innocuous appearing lesion with no pathognomonic features. Diagnosis is seldom made before operation and frequently misdiagnosed after operation We present our experienced with sebaceous carcinoma. female 45 years old, with history mass at her left hand grew rapidly during the past 4 months. At the beginning, there was a small wart over the little finger of her left hand that was not changing for the past 30 years. The patient then started scratching the wart until it fell off (1 year ago). The wound initially healed but then the same lesion grew back and became even larger. The patient repeated this habit and the lesion grew into its current size. The lesion itself started to bleed easily and became infected. During the past 4 months, patient also experienced the same lesion growing at her left index finger. Patient also complaint of pain which was localized to the lesion, non-radiating, and was felt increased when the patient scratched at the lesion. We performed resection of tumor and amputation at 4th and 5th fingers and also disarticulation at MCP joint 2nd finger and take a sample as histhopatological examination.